Amorphous Boron Suboxide - Durandurdu, Murat (Wiley, 2019)
We study the atomic structure and the electronic and mechanical properties of amorphous boron suboxide (B6O) using an ab initio molecular dynamic technique. The amorphous network is attained from the rapid solidification of the melt and found to consist of boron and oxygen-rich regions. In the boron-rich regions, boron atoms form mostly perfect or imperfect pentagonal pyramid-like configurations that normally yield the construction of ideal and incomplete B-12 molecules in the model. In addition to the B-12 molecules, we also observe the development of a pentagonal bipyramid (B-7) molecule in the noncrystalline structure. In the oxygen-rich regions, on the other hand, boron and oxygen atoms form threefold and twofold coordinated motifs, respectively. The boron-rich and oxygen-rich regions indeed represent structurally the characteristic of amorphous boron and boron trioxide (B2O3). The amorphous phase possesses a small band gap energy with respect to the crystal. On the bases of the localization of the tail states, we suggest that the p-type doping might be more convenient than the n-type doping in amorphous B6O. Bulk modulus and Vickers hardness of the noncrystalline configuration is estimated are be 106 and 13-18 GPa, respectively, which are noticeably less than those of the crystalline structure. Such a noticeable decrease in the mechanical properties is attributed to the presence of open structured B2O3 glassy domains in the amorphous model.
Durandurdu, Murat/0000-0001-5636-3183;
Keywords: Amorphous; Boron Suboxide; Hardness